Dancefloor-driven literature: subcultural big bangs and a new center for the aesthetic universe1. Issue 1 (13th December 2016) - Morrison, Simon A.
Abstract: This paper sets coordinates squarely for Holleran's 'aesthetic center of the universe' – venturing towards the black hole of the nightclub dancefloor. Further, it will investigate those writers determined to capture the electronic essence of this at times alien dance music culture within the rather more earth-bound parameters of the written word. How might such authors write about something so otherworldly as the nightclub scene? How might they write lucidly and fluidly about the rigid, metronomic beat of electronic music? What literary techniques might they deploy to accurately recount in fixed symbols the drifting, hallucinatory effects of a drug experience? In an attempt to address these questions this paper will offer an altogether outerspace overview of this subculture and its fictional literary output.